2006
DOI: 10.4267/pollution-atmospherique.1503
|View full text |Cite
|
Sign up to set email alerts
|

Élaboration d’un cadastre d’émissions interrégional pour la plate-forme de modélisation de prévisions cartographiques ESMERALDA

Abstract: Cet article présente la méthodologie appliquée pour la constitution du cadastre d'émissions d'ESMERALDA. Ce cadastre couvre un domaine comprenant cinq régions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The horizontal distribution of air pollutants at the European scale is also studied with CHIMERE chemistrytransport model simulations (Menut et al, 2013) from the inter-regional platform Esmeralda (EtudeS Multi RégionALes De l'Atmosphère, http://www.esmeralda-web.fr, Cortinovis et al, 2015). This model is run hourly and averaged at daily scale, with a horizontal resolution of 15 x 15 km 2 and 8 vertical levels between 40 m to 5 235 km.…”
Section: Regional Conditions From Satellite Data and Modelsmentioning
confidence: 99%
“…The horizontal distribution of air pollutants at the European scale is also studied with CHIMERE chemistrytransport model simulations (Menut et al, 2013) from the inter-regional platform Esmeralda (EtudeS Multi RégionALes De l'Atmosphère, http://www.esmeralda-web.fr, Cortinovis et al, 2015). This model is run hourly and averaged at daily scale, with a horizontal resolution of 15 x 15 km 2 and 8 vertical levels between 40 m to 5 235 km.…”
Section: Regional Conditions From Satellite Data and Modelsmentioning
confidence: 99%
“…In the present analysis, we use in situ gaseous ammonia measurements at surface level carried out with an AiRRmonia instrument (Mechatronics Instruments, the Netherlands) at the SIRTA observatory (Haeffelin et al, 2005). The principle of this instrument, described in Cowen et al (2004), is essentially based on conductimetric detection of ammonia that is first absorbed via a gas-permeable membrane and dissolved in water (i.e., in the form of ammonium ions, forming acidic solution). Several intercomparison exercises have shown that this procedure provides more accurate NH 3 measurements (Norman et al, 2009;von Bobrutzki et al, 2010).…”
Section: Surface In Situ Observations Of Ammonia and Aerosol Compositionmentioning
confidence: 99%